Supporting Success: Aboriginal Students in Higher Education - Gallop, Cynthia Justine; Bastien, Nicole (Canadian Journal of Higher Education, 2016)
For most Aboriginal students in Canada, the term “success” in postsecondary education is more complicated than the mainstream notions of higher socioeconomic status and career advancement. Historically, “success” for Aboriginal peoples in postsecondary education was linked to issues of assimilation, since to be “successful” meant Aboriginal students had to completely adapt to the mainstream values and behaviours of the mainstream postsecondary institutions. Today, higher education is recognized as an important tool for capacity building and assisting Aboriginal communities to achieve their goals of self-determination and self-government. This paper presents some of the findings of a qualitative study conducted in a midsized Canadian postsecondary institution. Findings from the study suggest that if Canadian postsecondary institutions are committed to retaining Aboriginal students, these institutions need to better understand how to create positive and supportive relationships between Aboriginal students and their peers and instructors. The development of these positive relationships then needs to be formalized and incorporated into both institutional planning and faculty instructional support.